Comparative Error Analysis In English Writing By First, Second, And Third Year Students Of English Department Of Faculty Of Education At Champasack University - SYCHANDONE, NOKTHAVIVANH (2016)
NokthavivanhSychandone. 2016. Comparative Error analysis in English writing by First, Second and Third year students of English Department at Champasack University. The study is focused on errors in students' writing and to identity namely: (1) the types of errors are made by students in 1st, 2nd, and 3rdyear of English department in their writing, (2) the frequencies of each types of error are made by students in year 1st, 2nd, 3rd of English department will make on their writing, (3) the differences and similarities of type of errors of learner on writing in first, second and third years, and (4) the sources of error on students' writing in year 1st, 2nd, 3rd. There are 54 students with 54 written task, they studied in different level (the first, second and third year). The quality is used this research to conduct the data. Thus total of error includes 571 erroneous sentences made by three levels. They are two types of errors, namely lexical errors (131 error sentences or 22, 94%) andsyntactical error (440 error sentences or 77, 05%), they have eight categories such as : (1) wrong word spelling , (2) wrong selection words, (3) false friend, (4) verb to be, (5) verb tenses, (6) preposition, (7) conjunction, and (8) sentences construction. There are twenty-three error cases. The researcher found the second year learners made more errors than first and third year, there are 263 errors sentences or 46, 05% whereas first year has 229 erroneous sentences or 40, 10% and third year has 79 erroneous sentences or 13, 81%. The similarities of errors categories have five verb tenses, preposition, sentence construction, wrong word spelling and wrong selection word. The difference of error categories have three, false friend words, verb "to be" and conjunction. The interlangusge influences to learners' error especially cognitive process then Selinker's theory is used to find error sources, thus it found that overgeneralization (265 errors or 46, 40%) is the main factor to make learners produce errors because learners have not understood tenses usage. Language transfer (199 errors or 34, 85%) is one factor that effect to learners' error, first language structure (Lao) influence in target language because xv learners forget the English language structure. The last factor affects to error, simplification (107 errors or 18, 73%) is omission some unnecessary words in sentences and incorrect form. The teachers should have more activities about writing practice in the classroom before beginning the lesson or the end of the class (on the paper) and have time limitation. After that, teachers must check the correct and feedback to learners in the next time or teachers find other activities which are stimulated them. Moreover, teachers should focus on the grammatical structure and vocabulary then they explain the different Lao grammatical rule and English grammatical rule. Keyword: comparative, error analysis, interlanguage, grammar, writing.